Private International Law in Mainland China, Taiwan and Europe. - Basedow, Jürgen (Materialien zum ausländischen und internationalen Privatrecht., 2014)
Over the last decades, private international law has become the target of intense codification efforts. Inspired by the stimulating initiatives taken by some European countries, by the Brussels Convention and the Rome Convention, numerous countries in other regions of the world started to enact comprehensive legislation in the field. Among them are Taiwan and mainland China. Both adopted statutes on private international law in 2010. In light of the rising significance of the mutual economic and societal relations between the jurisdictions involved and of the legal innovations laid down in the.